Homogeneous catalysts : activity-stability-deactivation - Leeuwen, P. W. N. M. van (Piet W. N. M.); Chadwick, John C.; Wiley InterScience (Online service) (Weinheim : Wiley-VCH Verlag, 2011)
This first book to illuminate this important aspect of chemical synthesis improves the lifetime of catalysts, thus reducing material and saving energy, costs and waste. The international panel of expert authors describes the studies that have been conducted concerning the way homogeneous catalysts decompose, and the differences between homogeneous and heterogeneous catalysts. The result is a ready reference for organic, catalytic, polymer and complex chemists, as well as those working in industry and with/on organometallics.
Elementary Steps -- Early Transition Metal Catalysts for Olefin Polymerization -- Late Transition Metal Catalysts for Olefin Polymerization -- Effects of Immobilization of Catalysts for Olefin Polymerization -- Dormant Species in Transition Metal-Catalyzed Olefin Polymerization -- Transition Metal Catalyzed Olefin Oligomerization -- Asymmetric Hydrogenation -- Carbonylation Reactions -- Metal-Catalyzed Cross-Coupling Reactions -- Alkene Metathesis.
Includes bibliographical references and index.
Print version record.
Keywords: Catalysts; Alkenes; Alkenes; Catalysts; SCIENCE -- Chemistry -- Physical & Theoretical; Alkenes; Catalysts; Electronic books